FORMULASI STRATEGI PENGEMBANGAN DESTINASI PARIWISATA DENGAN MENGGUNAKAN METODE ANALISIS SWOT: STUDI KASUS KAWASAN PECINAN KAPASAN SURABAYA - Rizki Adityaji (Universitas Merdeka Malang, 2018)
This study aims to find out the strategy to develop the Chinatown area of Kapasan Surabaya as tourism destination using the SWOT analysis tools. The strengths, weaknesses, opportunities and threats of Kapasan as one of the oldest tourism attraction in Surabaya will be analyzed comprehensively. From the study, it is expected to obtain strategic formula to develop the Chinatown area of Kapasan to be well known tourist attraction by local and international visitors.